Character Development Creativity in Unit Blocks for Visual Spatial Intellegence Improvement of Children with Special Needs - Muhammad Imam Tobroni (Bina Nusantara University, 2017)
Autism is a neurodevelopmental disorder that is present from birth or early childhood. People with autism usually have impaired social interaction, difficulties in verbal and non- verbal communication, and repetitive behaviour. One of the forms of autism treatment is therapy. Vision therapy through toys that require concentration and creativity is able to treat autism as it won’t limit the imagination of children with the disorder. Toys usually have their own patterns and programs that tend to limit children’s creativity, imagination and visual and spatial intelligence. This can lead to children’s stress and lack of confidence. A character design on unit block toys is a form of vision therapy. It develops children’s visual and spatial creativity and intelligence. It also helps children to be independent and helps with their perception. Unit blocks consist of pieces of wooden blocks with different shapes and sizes that can form even bigger shapes, based on children’s imagination and ability to design a space or a building. Children’s visual and spatial intelligence help them visualize and notice shapes, colours, spaces, and designs of the unit blocks accurately, modify their surroundings based upon their perceptions, and recreate the aspects of their visual experiences. Playing Lego blocks will help develop the visual spatial intelligence of children with autism as it stimulates their ability to express ideas and to design a character the way they like.